Highlight, Write, Elaborate: Note-Taking Strategies to Master Reality-Based Mathematical Tasks - Wienecke, Lisa-Marie; Leiss, Dominik; Ehmke, Timo (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This study investigates the effect of note-taking strategies on solving reality-based mathematical tasks, such as highlighting relevant information, writing relevant data, and elaborating on information during the solution process. While prior research has highlighted the general benefits of note-taking for learning, few studies have examined how specific note-taking strategies operate within the context of complex, reality-based mathematics tasks. This study extends existing work by systematically analyzing how different note-taking subprocesses interact with student characteristics and influence solving success. Data of 1064 task solutions from students in grades 7–10 (Mage = 14.85, SDage = 1.26) were collected from three task contexts, each at three levels of language, and coded for subprocesses, namely, relevant and irrelevant notes, calculation paths, and elaboration strategies. The methodology included descriptive statistics, correlation analyses corrected for multiple comparisons and generalized linear mixed models to explore the relationship between note-taking strategies, personal factors (e.g., mathematical and language proficiency), and task performance. Effective note-taking strategies, such as writing and elaborating relevant information, significantly contributed to correct task solutions. Conversely, taking irrelevant notes was negatively associated with performance. The generalized linear mixed models indicated that personal characteristics, including general mathematics and language proficiency, predicted task success, text understanding, and various note-taking types. Effective note-taking enhanced students’ capacity to tackle complex problems. These findings address previous calls to examine in detail the subprocesses of solution strategies and underscore the importance of teaching different note-taking strategies to enhance the solving process in reality-based tasks.

Diese Studie untersucht die Zusammenhänge zwischen den Notizenstrategien im Lösungsprozess, wie dem Hervorheben relevanter Informationen, dem Aufschreiben relevanter Daten und dem Elaborierend von Informationen, und dem Lösen realitätsbezogener Aufgaben. Während frühere Untersuchungen das Anfertigen von Notizen für das Lernen hervorgehoben haben, gibt es nur wenige Studien, die untersucht haben, wie bestimmte Notizen im Kontext des Lösungsprozesses realitätsbezogener Mathematikaufgaben wirken. Die vorliegende Studie erweitert den bestehenden Forschungsstand, indem sie systematisch analysiert, wie verschiedene Teilprozesse, wie beispielsweise das Hervorheben zur Lösung benötigter Informationen und das Elaborieren jener, mit den Merkmalen der Lernenden interagieren und der Aufgabenleistung beeinflussen. Die Daten von 1064 Aufgabenlösungen von Lernenden der Klassen 7 bis 10 (age = 14,85, SDage = 1,26) wurden anhand von drei Aufgabenkontexten mit jeweils drei Sprachniveaus erhoben. Die Analysen umfassen deskriptive Statistiken, korrigierte Korrelationsanalysen und lineare gemischte Modelle (GLMM), um den Zusammenhang zwischen Notizstrategien, Personenmerkmalen (z. B. mathematische und sprachliche Kompetenzen) und der Aufgabenleistung zu untersuchen. Strategien, wie das Aufschreiben und Elaborieren relevanter Informationen, trugen signifikant zur korrekten Lösung der Aufgaben bei. Umgekehrt ist das Notieren irrelevanter Informationen negativ mit der Leistung verbunden. Die GLMM zeigten, dass persönliche Merkmale, darunter allgemeine Mathematik- und Sprachkenntnisse, das Textverständnis und verschiedene Arten der Notizen den Erfolg beim Lösen der Aufgabe vorhersagen. Diese Ergebnisse entsprechen früheren Forderungen, die Teilprozesse von Lösungsstrategien im Detail zu untersuchen, und unterstreichen die Bedeutung des Unterrichtens verschiedener Notizen-Strategien, um den Lösungsprozess bei realitätsnahen Aufgaben zu verbessern.
Hervorheben, Herausschreiben, Elaborieren: Notizenstrategien um den Herausforderungen des Lösens realitätsbezogener Aufgaben zu begegnen
Keywords: Mathematical Modelling; Elaboration Strategies; Word Problems; Note-taking; Organization Strategies; Language Competence; Mathematisches Modellieren; Elaborationsstrategien; Realitätsbezogene Aufgaben; Notizen; Organisationsstrategien; Sprachkompetenz